Enhanced Chlorophyll Degradation Triggers the Pod Degreening of “Golden Hook,” a Special Ecotype in Common Bean (Phaseolus vulgaris L.) - Hu, Bo; Zhu, Jinlong; Wu, Hongyan; Xu, Kun; Zhai, Hong; Guo, Ning; Gao, Yi; Yang, Jiayin; Zhu, Danhua; Xia, Zhengjun (Frontiers in Genetics, 2020)
To reveal genetic factors or pathways involved in the pod degreening, we performed transcriptome and metabolome analysis using a yellow pod cultivar of common bean-‘Golden Hook’ ecotype, and its green pod mutants yielded via gamma radiation. Transcriptional profiling showed expression levels of red chlorophyll catabolite reductase (RCCR, Phvul.008G280300) involved in chlorophyll degradation was strongly enhanced at early stage (2 cm long) in wild type but not in green pod mutants. The expression levels of genes involved in cellulose synthesis was inhibited by the pod degreening. Metabolomic profiling showed the content of most flavonoid, flavones and isoflavonoid was decreased during pod development, but the content of afzelechin, taxifolin, dihydrokaempferol and cyanidin 3-O-rutinoside was remarkably increased in both wild type and green pod mutant. This study revealed that the pod degreening of golden hook resulted from chlorophyll degradation, could trigger changes in cellulose and flavonoids biosynthesis pathway, offering this cultivar special color appearance and good flavor.